Eco-Education in Pesantren: Analyzing Green Discourses Through Ecolinguistic Approach - Fitriatul Masitoh; Mufti Rasyid (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
Pesantren possesses a plus value to boost the idea of “go green” through its education system. Forest Watch reveals that Indonesia has lost its 18,91 millions hectare of forest since 2001 till 2014. In other words, Indonesia is on the fifth rank getting away from its big canopies. Based on this matter, some pesantren in Indonesia has taught their students to love their nature by doing real actions. Pondok Pesantren Al-Yasini in Pasuruan, Roudlotut Tholibin in Bojonegoro, Assiddiqiyah 11 in Lampung, Nu War in Bekasi, and Ridho Alloh in Temanggung have been taking an action to plant hundred thousands of trees. These achievements are pronounced through online mass media using the power of language to inspire audiences as campaign. The reciprocal correlation between environment and language is examined through an eco-linguistic study. Here, the change of language used represents the ecological change. Having to do with this issue, this dialectical ecolinguistic analysis is intended to elaborate lingual units standing for certain meanings. Collecting the data through green discourse news texts, this study confirms that dialectical eco-linguistic approach, covering three dimensions of social praxis i.e., ideological, social, and biological dimensions, related with eco-pesantren influences the people involved i.e. its speakers and readers; therefore, their attitude toward the environment is constructive e.g. being eager in planting trees